L’Artiste et son art qui vient de loin... Gérard de Nerval et son "Voyage en Orient" (1850-1851) - Sosień, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2019)
In the third and last part of Voyage en Orient 1850-1851, entitled L’Histoire de la Reine de Saba et de Soliman, prince des génies (The History of the Queen of Sheba and Soliman, prince of the geniuses), Gérard de Nerval creates a figure of Adoniram, the brilliant sculptor and architect of the Temple of Jerusalem, in the service of King Solomon. The half-biblical, half-legendary Adoniram is a mysterious, independent artist who is inconceivable to create under the dictates of any authority and power. His art reflects the pursuit of the absolute and the creation of great works that undermine all the principles of mimicism and categories of rationality. Loneliness, despair and suffering are not so much the price of genius as the testimony of one of the stigmata of the romantic artist.